Comparative Study Entered New Approach FMV and Control SFR for Active Compensation of Harmonic Currents in Shunt Active Power Filter - Loutfi Benyettou (Institute of Advanced Engineering and Science, 2018)
In this article, we discuss the problem of degradation of current in electrical installations, which follows directly from the proliferation of non-linear loads, to solve it, we used a two-level inverter as a parallel active filter, which injects current harmonics at the connection point with two compensation methods the method of instantaneous active and reactive power (pq method and pq method with MVF) method binds to the repository synchronization. We will highlight two control strategies by hysteresis and PWM. Simulation results using Blok set Power System (PBS)/ Simulink Matlab show reduced THD in accordance with standard IEEE-519.